Chemical Studies on Human Breast Milk. - Jeje, Temitayo Enitan (Obafemi Awolowo University, 2014)
The variation in some chemical constituents of human breast milk from the first month to the fifteenth month of' breast-feeding was studied. Deductions were then made as to the effect this variation had on the nutritional status of the children whose mothers' breast milk was collected. This study was done on milk samples collected from nursing mothers of children who were healthy and of those who were malnourished.